2016
DOI: 10.4238/gmr.15027406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of siRNA-induced silencing of cellular prion protein on tyrosine hydroxylase expression in the substantia nigra of a rat model of Parkinson’s disease

Abstract: ABSTRACT. The most significant pathological feature of Parkinson's disease (PD) is the progressive degeneration of dopaminergic (DA) neurons in the substantia nigra. Currently, available treatments for PD cannot prevent the loss of DA neurons. Tyrosine hydroxylase (TH) expressed in substantia nigra neurons catalyzes the conversion of tyrosine to L-3,4-dihydroxyphenylalanine (L-DOPA), which is the rate-limiting step of DA biosynthesis. Major reasons for PD occurrence include decreased TH activity in the substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…PrP expression in CSF should be detected in a larger number of PD patients, and the impact on the PD model of overexpression of PrP or deletion of PrP also requires further investigation. Exciting results have illustrated the effect of PrP on PD in a rat model via siRNA silencing of cellular prion protein (Wang et al, 2016). Further studies could utilize similar gene-editing tools to elucidate the potential of CSF PrP in the clinical diagnosis of PD and PD with RBD.…”
Section: Discussionmentioning
confidence: 99%
“…PrP expression in CSF should be detected in a larger number of PD patients, and the impact on the PD model of overexpression of PrP or deletion of PrP also requires further investigation. Exciting results have illustrated the effect of PrP on PD in a rat model via siRNA silencing of cellular prion protein (Wang et al, 2016). Further studies could utilize similar gene-editing tools to elucidate the potential of CSF PrP in the clinical diagnosis of PD and PD with RBD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the occurrence and development of Pd are related to the environment, genetics, metabolic deficiency, oxidative stress and neuroinflammatory response (2,7,8). reportedly, inhibition of tyrosine hydroxylase (TH) activity was found to be closely related to the occurrence of Pd, and immunohistochemical determination of TH expression has provided an essential tool for visualization and quantification of the damage and loss to dopaminergic neurons in Pd models (9,10). additionally, an in vitro study by Salemme et al (11) indicated that dihydroasparagusic acid can alleviate neurodegenerative diseases by inhibiting inflammatory and oxidative processes.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models are essential in experimental medical science to investigate etiology, mechanisms and symptoms of human diseases as well as new potential therapeutic strategies. For PD, the 6-hydroxydopamine (6-OHDA) rat model has proven to be a valuable tool in understanding the underlying mechanisms of the disease and in the establishment of new therapies [16][17][18][19][20]. It belongs to the toxin-induced models and is based on the uni-or bilateral intracerebral injection of 6-OHDA into the medial forebrain bundle, the substantia nigra pars compacta, or subregions of the caudate-putamen complex.…”
Section: Introductionmentioning
confidence: 99%